Features of Asthenic Syndrome and Autonomic Disorders in Children with Community-Acquired Pneumonia - S.L. Niankovskyi; I.V. Babik (Zaslavsky O.Yu., 2015)
The article provides the results of the first in Ukraine study of autonomic disorders and manifestations of asthenic syndrome in schoolchildren diagnosed with community-acquired pneumonia. The research involved 120 children of both sexes. The study was an open-label, single-center. All children included in the survey were admitted to hospital on the 2nd - 4th days at the height of clinical symptoms of community-acquired pneumonia. A high percentage of manifestations of asthenic syndrome (in 100 % of children) and of autonomic disorders was noted that require some correction of treatment in future.